What does “language” mean for its users? Constructing a theoretical model of a notion of language in the public space - Vukotić, Vuk (Taikomoji kalbotyra, 2016)
Research into language ideologies is a fast growing field of research, especially within its critical paradigm, highlighting reproductions of dominant and often repressive ideologies about language (racism, sexism, nationalism, etc.). On the other hand, the other, cognitive paradigm has contributed to the field of language ideology by way of closer insights into the world of the speaker, providing a more subtle understanding of the cognitive processes at work behind attitudes to language and ideologies of language. Some of the studies employing the cognitive approach have also looked to how “language” is conceptualised in public discourse. In spite of the differences in the material and the foci in these studies, re-occurring patterns have begun to emerge. This paper offers a systematic review of these studies in order to answer the question “What elements of notions of language have been identified in the research on public debates about language?”. The aim of this review is to create a theoretical model of the “public notions of language”, which would explain differences in understanding of language in public debates. A total of 12 studies examining public notions of language have been collected, analysed and their findings synthesized into a model of a public notion of language. Three key elements construct the notion of language: (1) the function of language, (2) the identification of linguistic expertise, or who the bearer of true/good language is and (3) the identification of language variety which is representative of the language users.